La casa de Bernarda Alba - García Lorca, Federico, 1898-1936 (Letras hispánicas, 1994)
In turn-of-the-century rural Spain, a newly widowed mother represses her five daughters by enforcing an eight year mourning period. This edition features a comprehensive introduction to Garcia Lorca and his play.